Analisis Pola Asuh Orang Tua Terhadap Hasil Belajar Matematika Siswa Kelas V SD N 02 Jolotigo Pekalongan - Dwi Novitarini; Qoriati Mushafanah; Sunan Baedowi (STKIP Andi Matappa Pangkep, 2022)
This research use desciptive qualitative approach. The instruments used were interviews, questionnaires and documentation, the subjects of this study were fifth grade students consisting of 16 male students and 9 female students, class teachers and parents of fifth grade students at SD N 02 Jolotigo, Talun District, Pekalongan Regency. The results of the interview with the fifth grade teacher found that there were problems with learning outcomes, especially mathematics. This study aims to determine how the parenting style of the mathematics learning outcomes of fifth grade. The results showed that there are three aspects of parenting skills that have not been mastered on the indicators of authoritarian parenting. Parents give full freedom for children to behave aggressively. Permissive parenting, parents do not pay attention to the interests/needs of children. Authoritative parenting, parents require children to meet high standards of responsibility to the family. Based on the results it was concluded that parenting patterns were good, this can be seen from the results of interviews where 85% had filled out well. The suggestion that researchers can convey is that teachers are expected to motivate students to be more active so that students in the future can be more motivated in learning.